The potential of biomass waste in Malaysian palm oil industry: a case study of Boustead Plantation Berhad - Jafri, Nur Huda Syazwani; Jimat, Dzun Noraini; Mohamed Azmin, Nor Fadhillah; Sulaiman, Sarina; Ahmad Nor, Yusilawati (IOP Publishing, 2021)
The oil palm industry is known as the primary producer of biomass in Malaysia. The massive production of oil palm biomass has resulted in a significant waste disposal problem.This study aims to assess the potential of waste derived from oil palm plantationsand processing mills to be transformed into value-added products for various applications. The study was conducted on three oil palm estates managed by Boustead Rimba Nilai Berhad using data on the generation rates of fresh fruit bunches (FFB), crude palmoil (CPO), and oil palm biomass waste from 2018 to 2020. The availability of FFB, CPO, empty fruit bunches (EFB)and excess fibers, and palm oil mill effluents (POME) in 2030 was predicted using a forecasting approach, with trend analysis as the tool of choice. From 2018 to 2020, the output of FFB, EFB and excess fibers, as well as POME grew by 16%, 14%, 23%, and 14%respectively. Based on trend analysis, the projection of FFB, CPO, EFB and excess fibers, and POME outputs in 2030 is expected to be 80%, 56%,92%, and 56% respectively, which are greater than the figuresrecorded in 2020. The state of the palm oil industry in Malaysia was described in this study andalso highlighted the potential of oil palm biomass in various industries and as a source of green energy. Oil palm biomass can be commercialized in a wide range of value-added products.